Is exclusive breastfeeding for six-months protective against pediatric tuberculosis? - León-Sandoval, Segundo (2021)
Experts recommend exclusive breastfeeding from birth to six months because it protects against deadly childhood illness, including respiratory tract infections and diarrhea. We hypothesized that exclusive breastfeeding would decrease the risk of active tuberculosis (TB) in children. We analyzed cross-sectional data from 279 children in Lima, Peru aged 6 to 59 months with TB symptoms and a close adult contact with TB. Mothers self-reported breastfeeding, and children were evaluated for TB per national guidelines. To quantify the association between exclusive breastfeeding and TB, we estimated prevalence ratios using a generalized linear model with a log link, binomial distribution, and robust variance. Twentytwo percent of children were diagnosed with TB and 72% were exclusively breastfed for six months. We found no evidence that six months of exclusive breastfeeding was associated with TB disease in either bivariate analyses (prevalence ratio [PR] = 1.5; 95%CI = 0.8–2.5) or multivariable analyses adjusting for sex and socioeconomic status (adjusted PR = 1.6; 95% [CI] = 0.9–2.7). In post hoc analyses among children whose close TB contact was their mother, we found evidence of a weak positive association between breastfeeding and TB (aPR = 2.1; 95%[CI] = 0.9–4.9). This association was not apparent among children whose close contact was not the mother (aPR = 1.2; 95%[CI] = 0.6–2.4). Our results raise the possibility that children who are breastfed by mothers with TB may be at increased risk for TB, given the close contact. Due to the cross-sectional study design, these results should be interpreted with caution. If these findings are confirmed in longitudinal analyses, future interventions could aim to minimize TB transmission from mothers with TB to breastfeeding infants